Four factor factorial design on residual curvatures of metal round bars in cross-roll straightening process - Roy, Sanjib; Pal, Arun (Journal of Production Engineering, 2025)
Straight round bars are widely used as raw materials in numerous industrial applications; however, they are frequently delivered in a bent condition, making straightening a necessary preparatory step to ensure consistent product quality. Achieving acceptable levels of residual curvature after straightening is essential, as excessive deviation can affect subsequent machining and assembly processes. This study explores the use of statistical Factorial Design to support decision-making and establish reliable quality criteria related to residual curvature. The applicability of Three-Factor and Four-Factor Factorial Designs is assessed to determine the influence of key process parameters and their interactions on straightening performance. The results provide insights that can help improve process optimization and support the selection of bar lots that meet required curvature tolerances.